The Correlation Between Blood Pressure, Basic Anthropometric Measurements, Hemoglobin, Hematocrit, Blood Sugar, and Uric Acid With Grip Strength in Elderly Women - Susy Olivia Lontoh; Ernawati Ernawati; Alexander Halim Santoso; Stanislas Kotska Marvel Mayello Teguh; Geoffrey Christian Lo; Nicholas Setia (Jurnal Kesehatan Amanah, 2025)
Grip strength is a key indicator of muscle function and health in elderly women, influencing mobility and independence. Factors such as blood pressure, body composition, and metabolic biomarkers influence grip strength. This study examines the relationship between blood pressure, anthropometric measurements, hemoglobin, hematocrit, blood sugar, and uric acid with grip strength. A cross-sectional study was conducted on 34 elderly women (mean age: 72.24 years) in the St. Asisi Elderly Community, Tebet. Blood pressure, anthropometric parameters, and venous blood samples were analyzed. Grip strength was assessed using the Camry Electronic Hand Dynamometer. Statistical analysis used the Spearman correlation test (p < 0.05). Age showed a significant negative correlation with right-hand (p = 0.023) and average grip strength (p = 0.026), indicating muscle decline with age. Other factors, including blood pressure, hemoglobin, hematocrit, blood sugar, and uric acid, had no significant correlations. Among anthropometric measures, calf circumference showed the strongest positive correlation with grip strength (p = 0.063). Age is the primary factor affecting grip strength in elderly women, with weak or no significant associations for other parameters. Strength training and neuromuscular conditioning may help mitigate age-related muscle decline and support functional independence.